A prospective study on the role of immunotherapy in metastatic cancer patients at Combined Military Hospital Dhaka - M. Quadrat E. Elahi (International Journal of Research in Medical Sciences, 2023)
Background: Immunotherapy is a treatment that uses a person’s immune system to fight cancer. Immunotherapy can boost or change how the immune system works so it can find and attack cancer cells. Among several cancers, metastatic cancer causes high mortality, and immunotherapies are expected to be effective in the prevention and treatment of metastatic cancer patients. In Bangladesh, we do have not enough research-based information regarding the role of immunotherapy in treating metastatic cancer patients. This study aimed to assess the role of immunotherapy in treating metastatic cancer patients. Methods: This prospective observational study was conducted in combined military hospital Dhaka, Bangladesh during the period from 26 March 2021 to 21 July 2022. In total 19 patients with metastatic cancer were enrolled in this study as study subjects. Proper written consent was taken from all the participants before data collection. Two (02) different outcomes were studied in this study; progression-free survival (PFS) and side effect percentages. A predesigned questionnaire was used in data collection. All data were processed, analyzed, and disseminated by using MS excel and SPSS version 23 program as per necessity. Results: In using pembrolizumab, side effects, fatigue, nausea, and decreased appetite were found 43%, 22%, and 20% lesser respectively than chemotherapy which was noticeable. In using nivolumab, as a side effect, skin rash was found 66% lesser than chemotherapy. Besides this, itching, face swelling, and apnea was found 33% lesser. On the other hand, in using atezolizumab, as side effects, swelling of arms and constipation were found 66% lesser, and itching, as well as apnea, was found 33% lesser than that in chemotherapy. At the 6-month follow-up we observed that in the nivolumab and atezolizumab treated groups 66% of cases survived separately whereas, in pembrolizumab treated group, 61% survived. Conclusions: In this study in all treatment groups, side effects were found as lesser than that in using chemotherapy. No major complication of any patients was observed in this study. So, can conclude that immune checkpoint inhibitors (ICIs) are better choice for metastatic diseases and ICIs exert lesser side effects than conventional chemotherapies.